Enhanced recovery pathways improve postoperative outcomes in haemorrhoid surgery: a narrative review - Kraft, Alin; Moldovan, Cosmin Alec; Rusu, Elena; Cochior, Daniel (Frontiers in Surgery, 2026)
Haemorrhoid surgery, while typically performed as a low-risk outpatient procedure, is frequently associated with considerable postoperative discomfort, delayed return to daily activities, and occasional unplanned healthcare visits. Enhanced recovery protocols, originally developed to improve outcomes in major abdominal surgery, offer a structured, evidence-based framework for optimizing perioperative care and accelerating recovery. This review explores whether these principles can be effectively applied to the context of haemorrhoidectomy. Key components such as patient education, multimodal pain control, minimal preoperative fasting, early mobilization, and structured discharge planning are conceptually well-suited to the needs of patients undergoing benign anorectal surgery. Early clinical experiences and extrapolated data from related surgical settings suggest that even minor procedures may benefit from standardized recovery pathways, with reported reductions in postoperative pain scores of up to forty percent, faster return to function by two to three days, and nearly fifty percent fewer unplanned return visits. These findings support the potential for improved pain management, reduced variability in care, and enhanced patient satisfaction. However, current evidence remains limited, with few studies specifically addressing the impact of enhanced recovery protocols in haemorrhoidectomy. This article synthesizes the available literature, highlights potential advantages and implementation challenges, and advocates for the development of a simplified, procedure-specific perioperative pathway tailored to the characteristics of this common surgical intervention. The integration of digital follow-up tools and individualized care strategies may further support recovery and reduce complications in this setting. Overall, a targeted and pragmatic approach to enhanced recovery in haemorrhoid surgery represents a clinically meaningful opportunity to improve outcomes and modernize care delivery in proctology.